2017
DOI: 10.1038/nchembio.2389
|View full text |Cite
|
Sign up to set email alerts
|

Functional selectivity of GPCR-directed drug action through location bias

Abstract: G protein-coupled receptors (GPCRs) are increasingly recognized to operate from intracellular membranes as well as the plasma membrane. The β2-adrenergic GPCR can activate Gs-linkedcyclic AMP (cAMP) signaling from endosomes. We show here that the homologous human β1-adrenergic receptor initiates an internal Gs-cAMP signal from the Golgi apparatus. By developing a chemical method to acutely squelch G protein coupling at defined membrane locations, we demonstrate that Golgi activation contributes significantly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
250
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(290 citation statements)
references
References 49 publications
(57 reference statements)
10
250
2
Order By: Relevance
“…A significant portion of AMPAR s are synthesized in the endoplasmic reticulum ( ER ) in dendrites possibly without TARP s, which might associate with the AMPAR core in a later secretory compartment (e.g., recycling endosomes ( RE s)) or the plasma membrane (Bowen et al, ). Surface insertion via RE s is promoted by intracellular norepinephrine ( NE ) signaling, which is transported from the extracellular space via the OCT 3 transporter first into the cytosol and then, as proposed here, into the lumen of RE s, analogous to NE transport into the Golgi apparatus (Irannejad et al, ). This NE transport enables intracellular stimulation of β 2 AR s that are associated with GluA1 in RE analogous stimulation of β 2 AR s in endosomes (Tsvetanova & von Zastrow, ).…”
Section: Regulation Of Ampars By Akap5‐anchored Pka and Pp2b During Vmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant portion of AMPAR s are synthesized in the endoplasmic reticulum ( ER ) in dendrites possibly without TARP s, which might associate with the AMPAR core in a later secretory compartment (e.g., recycling endosomes ( RE s)) or the plasma membrane (Bowen et al, ). Surface insertion via RE s is promoted by intracellular norepinephrine ( NE ) signaling, which is transported from the extracellular space via the OCT 3 transporter first into the cytosol and then, as proposed here, into the lumen of RE s, analogous to NE transport into the Golgi apparatus (Irannejad et al, ). This NE transport enables intracellular stimulation of β 2 AR s that are associated with GluA1 in RE analogous stimulation of β 2 AR s in endosomes (Tsvetanova & von Zastrow, ).…”
Section: Regulation Of Ampars By Akap5‐anchored Pka and Pp2b During Vmentioning
confidence: 98%
“…One important question is how norepinephrine (NE), the main endogenous β AR agonist in the brain, can control trafficking of AMPAR–β 2 AR complexes from inside neurons to the surface. Recent work shows that NE is transported into the cell and from the cytosol into the lumen of intracellular vesicles via the transporter OCT3, which allows stimulation of β ARs inside cells (Tsvetanova & von Zastrow, ; Irannejad et al, ). We propose that NE accesses the lumen of recycling endosomes (REs), which contain recycled as well as newly synthesized AMPARs (Bowen et al, ), where it stimulates the β 2 ARs associated with AMPARs to trigger S845 phosphorylation (Fig ).…”
Section: Regulation Of Synaptic Ampar Trafficking By β2 Ar Signalingmentioning
confidence: 99%
“…Evidence that the intracellular receptor pool produces a functional response via cytoplasmic G proteins emerged by comparing effects of membrane‐permeant and ‐impermeant ligands on calcium signaling; membrane‐impermeant antagonists only partially blocked the cellular calcium response induced by glutamate, and a full response to glutamate required organic anion transporter and/or exchanger activities that enable this ligand to cross membranes . The beta‐1 adrenergic receptor was found to be activated by its physiological agonist, epinephrine, at the Golgi apparatus of cardiac muscle cells, and ligand access was found to require an organic cation transporter activity . Sufficiently hydrophobic ligands, such as the clinically relevant drug dobutamine, were found to selectively activate the Golgi‐associated pool of adrenergic receptors when transporter was inhibited.…”
Section: G Protein Signaling From the Biosynthetic Pathwaymentioning
confidence: 99%
“…However, this is likely to be an oversimplification as generation of only a few second messengers by over 800 GPCRs and a plethora of different ligands appears insufficient to explain the complex signalling and vast range of different physiological outcomes that are observed both in vitro and in vivo. Recent studies have revealed the importance of the texture of the initiated intracellular signal in controlling unique physiological outcomes, including both spatial (i.e., subcellular compartmentalisation of the signal) and temporal (i.e., changes in the signal over time) properties (Calebiro et al, ; DeFea, ; Godbole, Lyga, Lohse, & Calebiro, ; Irannejad et al, ; Irannejad et al, ; Kotowski, Hopf, Seif, Bonci, & von Zastrow, ; Mullershausen et al, ; Nikolaev, Bünemann, Schmitteckert, Lohse, & Engelhardt, ; Tsvetanova & von Zastrow, ; Wehbi et al, ). These shifts in the way we understand canonical GPCR activation and downstream signalling are already opening exciting new avenues for drug discovery (Jensen et al, ; Jimenez‐Vargas et al, ; Yarwood et al, ).…”
Section: G‐protein Coupled Receptorsmentioning
confidence: 99%